PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA GOLDEN SUPERMARKET MANADO - Juwita Elisabeth Poluan; William Agustinus Areros; Aneke Punuindoong (JURNAL ADMINISTRASI BISNIS, 2017)
ABSTRAK. Given the number of malls and supermarkets (supermarket) which is located in the same area, then by itself would give birth to the fierce competition to seize visitors and buyers. Additionally the competition also came from some retailers in traditional markets and shops are scattered in the same area. Golden Supermarkets is one of the famous retail among some retail in the city of Manado. In the motion of daily operations, Golden Supermarkets as shopping centers provide a variety of different goods with different types, brands and sizes at varying price levels. Problem formulation, Based on the background outlined above, then the problem is: What is the quality of services that includes Tangible, Realibility, Responsiveness, Assurance, and Empathy effect on customer satisfaction in the Golden Supermarket Manado.Objective, while the objectives of this research is to determine how much the quality of the services provided by Golden Supermarket. "Quality of service refers to judgments of customers about the core of this service and the service provider itself or the entire service organization, most people are now beginning to show demand towards service excellence, they are no longer just need a quality product, but they prefer to enjoy the convenience of service "The method used in this research is descriptive quantitative method in accordance with the purpose of the research presented in advance outlining the nature of the nature and looking for a systematic description of the facts under investigation From the discussion above results show that the performance of the services provided by the service provider is very influential on consumer satisfaction, the strategy adopted by a Golden Supermarket Manado, especially in the service sector should be implemented properly. It can be concluded, responsiveness (Responsiveness) is a variable that shows the desire and willingness of employees Golden in providing services to consumers Golden. The management of Golden should provide great motivation for all employees of Golden supports the activities of service to consumers in adil.Akan better if the motivation given to employees of Golden in the form of rewards according to ability.Keywords: Quality, Service, and Satisfaction